Transition from antiferromagnetic ground state to robust ferrimagnetic order with Curie temperatures above 420 K in manganese-based antiperovskite-type structures. Issue 48 (5th December 2018) - Zhang, Xinghong; Yuan, Quan; Gao, Tangling; Ren, Yang; Wu, Hui; Huang, Qingzhen; Zhao, Jinggeng; Wang, Xianjie; Yuan, Ye; Xu, Chi; Hu, Yongfeng; Dynes, James J.; et al.
Abstract : Robust ferrimagnetic order is found in Mn3 Ga x N x when x = 0.5, 0.6, and 0.7 with Curie temperature in the range of ∼390–420 K. Abstract : Manganese (Mn)-based antiperovskite structures (Mn3 AX, where A and X represent the 3d transition-metal elements and N or C atoms, respectively) have attracted growing attention because of their novel electronic and magnetic properties. However, the lack of an effective approach to regulate the magnetic coupling in Mn3 AX crystal structure, particularly in antiferromagnetic ground states, hinders their further design and applications. Herein, robust high-temperature ferrimagnetic order with a Curie temperature ( T C ) in the range of ∼390–420 K was successfully achieved in Mn3 Ga x N x ( x = 0.5, 0.6, and 0.7) via composition-deficient engineering. A systematic investigation, including synchrotron X-ray diffraction, neutron powder diffraction, pair distribution function, X-ray absorption near-edge structure, magnetic characterization, and first-principles calculations, convincingly indicated that the redistribution of partial atoms in the antiferromagnetic ground state was responsible for the observed long-range magnetic order. These results not only provide a new perspective into the design and construction of high-temperature ferrimagnets based on the Mn3 AX structure, but also open up a promising avenue for the further design of Mn3 AX-based spintronic or other multifunctional devices.